The spies of Warsaw : [large type] : a novel - Furst, Alan (Thorndike Press, 2008)
A French aristocrat working as a military attache at the French embassy in Warsaw in 1937 tries to gather information for Poland and France, wondering what move Germany will make next. Romantic sparks fly between the French aristocrat's cousin and a Franco-Polish woman who works as a lawyer for The League of Nations, all against the backdrop of Hitler's gathering war.